Design a battery charger controller for electric vehicle (mechanical) - Mohd Hafizi, Shaarani (2009)
This report is an outcome of the work I have carried out in doing and completing my final year project, Design a Battery Charger Controller for Electric Vehicle (Mechanical). The paper presents another design of battery charger controller that potentially can be apart of an EV system or somehow an explanation on the idea of basic battery charger controller in EV development process. It is an electronically project which required knowledge in electric and electronic field. The overall duty is to analyze the previous design of battery charger controller circuits and come out with a better design as suggestion of the battery charger controller which using microcontroller as the controller of the controller. The report starts with an introduction on EV, the advantages and disadvantages. Then a further introduction describe on the variety of battery type and their suitability to be used in the project. After gathering all the relevant information, the project undergoes design process. The knowledge gathered before is used to make a design which refers to problem statements that suitable for the project. There are comparisons and considerations are made in the designing stage based on self ability and condition. The project follows with writing the programming for the microcontroller using Visual Basic software in C language. The circuit then will be test as it will be the result for the ability of solving the problem statements of the project. At the end, when all the process mentioned above is done, the material for report writing is gathered. The report writing process will be guided by the University Malaysia Pahang final year report writing guide. This process also included the presentation slide making for the final presentation of the project. The project ended after the submission of the report and the presentation slide has been presented.